2015
DOI: 10.1177/0963662515574986
|View full text |Cite
|
Sign up to set email alerts
|

Media sources, credibility, and perceptions of science: Learning about how people learn about science

Abstract: Knowledge about science and technology has become increasingly important in this age of digital information overload. It is also becoming increasingly important to understand what contributes to scientific learning, including information sources and trust in those sources. In this study, we develop and test a multivariate model to explain scientific knowledge based on past theories on learning from the news from the fields of political communication, sociology, and media psychology. We focus on the impact of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 64 publications
2
58
0
Order By: Relevance
“…Members of the general public with less interest in science may have a more difficult time gleaning scientific knowledge from the media than those with more interest (Takahashi and Tandoc, 2015). When considering their responsibility as scientists to communicate new results to the public (Fischhoff, 2013;Kueffer and Larson, 2014), VR researchers working in clinical applications must be careful to avoid language that might give false hope to patients.…”
Section: Vr Researchers Aiming At New Clinical Applications Should Thmentioning
confidence: 99%
“…Members of the general public with less interest in science may have a more difficult time gleaning scientific knowledge from the media than those with more interest (Takahashi and Tandoc, 2015). When considering their responsibility as scientists to communicate new results to the public (Fischhoff, 2013;Kueffer and Larson, 2014), VR researchers working in clinical applications must be careful to avoid language that might give false hope to patients.…”
Section: Vr Researchers Aiming At New Clinical Applications Should Thmentioning
confidence: 99%
“…Mass media and internet usage are also the factors that cause learning difficulties experienced by students (Chu, 2014;Takahashi & Tandoc, 2016). This can be indicated from the students' activities.…”
Section: E Difficulties In Learning Basic Competency 15: Identifyinmentioning
confidence: 99%
“…With the example of issues related to Stimulus-Triggered Acquisition of Pluripotency (STAP) cells [6], scientific news reporting via television tends to prioritize sensationalism over accurate scientific information. A previous study reported that there is no association between information acquisition via television and scientific knowledge, although information acquisition via the Internet is associated with scientific knowledge [7].…”
Section: Discussionmentioning
confidence: 99%